Legitimate priority-setting: refining accountability for reasonableness and its application within NICE - Rand, L (2016)
In this dissertation, I examine Daniels and Sabin’s theory for fair and legitimate procedures, accountability for reasonableness (AFR), and its relationship to the National Institute for Health and Care Excellence (NICE). AFR has been widely adopted as an exemplar model of procedural decision-making for healthcare limit-setting. Despite the prominence of AFR, few institutions have fully adopted it, so NICE, which claims AFR enhances its legitimacy, is an important example of how the theory translates into practice. The dissertation addresses challenges to AFR as a theory. I first argue that the substantive constraints in AFR’s procedure are left too vague to answer criticisms of the theory. I refine the definition of relevant reasons, focusing on mutual justifiability and raise a novel problem about whether agreement on reasons to determine their relevance is based on normative objective standards or empirical agreement. I also make a new argument that the four conditions of AFR are not sufficient for legitimacy. I argue that we need a condition of fair consideration in order to ensure legitimacy in limit-setting procedures that follow AFR. Fair consideration requires decision makers to take relevant reasons seriously. The latter part of the dissertation examines NICE’s adoption of AFR. As a public body NICE needs to demonstrate the legitimacy of its decisions, and it supports its claim to legitimacy with AFR as a framework of procedural justice. I argue that NICE meets the conditions of AFR, but it also supplements AFR with additional procedural principles, demonstrating that AFR is not specific enough and does not meet the needs of an actual priority-setting body. NICE strengthens its claims to legitimacy with its procedural principles, however it fails to implement fair consideration of reasons, so it misses out on an essential element for legitimacy, as I argue the revised account of AFR requires. NICE could further enhance its legitimacy with fair consideration. NICE’s application of AFR illustrates how problems in the theory translate into challenges for practice. I address some of these challenges to legitimacy with the additional requirement of fair consideration.